(untitled) (Research, Society and Development, 2021)
With an increasingly busy lifestyle, consumers are looking for convenience, with products that are easy and quick to prepare. In this context, we highlight the restructured meat products breaded like nuggets. The study aimed to develop and evaluate nuggets made with pork by a sensory method. Three formulations with different concentrations of swine fat were prepared. The microbiological evaluation of the formulations was carried out, which did not present microbial contamination. The sensory acceptability assessment was conducted using a 9-point hedonic scale for the attributes softness, flavor, aroma, crispness, appearance, and overall impression of the product. Also, to assess the opinion of consumers regarding the product, a 5-point purchase intention test was applied. The results obtained show that the three samples obtained a score greater than or equal to 7 (I liked it regularly) by more than 90% of the judges. No score lower than 5 were attributed to the formulations, indicating low rejection of the products. Purchasing intentions were also high, with the percentage of judges indicating scores 4 and 5, corresponding to the terms “probably would buy” and “certainly buy” was 86.4, 81.8, and 84.5% for sample A, B, and C, respectively. The work showed that pork-based nuggets with different fat contents obtained excellent acceptability and purchase intention, presenting themselves as a potential alternative for insertion in the consumer market.